New World of Work: How the Value System of Generation Z Is Changing Leadership - Jens BERGER (Communications of International Proceedings, 2023)
With Generation Z (GenZ) as the workforce of the future, companies in Germany face special challenges. This generation is unable to meet the increasing demand for skilled workers and managers to ensure competitiveness due to its low population share. There is a deficit on the labour market. They are therefore in great demand. Their divergent values and a lesser interest in traditional employment distinguish them significantly from others. Germany is home to the Silent, Boomer, X, Millennials (GenY) and the Z and Alpha generations (GenA). While some are just leaving working life (Boomers), others are just growing into it (GenZ), or are still too young (GenA). The study sheds light on the findings of generational research and brings them together with the research results of the labour market. The result serves as a decision-making aid for companies to align themselves with the future challenges of the labour market. Generation Z seeks job security but is not interested in long-term employment. Companies should have a clear vision and offer the possibility of self-realisation. Ideally, the working atmosphere is characterised by an individual leadership style. Supervisors take on the role of coach. This creates employee loyalty. Employment relationships should offer a balance between work and leisure. GenZ want flexibility in the workplace, part-time contracts and sabbaticals. They often come from families where they were supported from an early age. Companies that understand these needs secure the young talent of tomorrow.
Keywords: Labor market development; Generation Z; generational sequences; new value system